Development of Agonist-Based PROTACs Targeting Liver X Receptor - Xu, Hanqiao; Ohoka, Nobumichi; Yokoo, Hidetomo; Nemoto, Kanako; Ohtsuki, Takashi; Matsufuji, Hiroshi; Naito, Mikihiko; Inoue, Takao; Tsuji, Genichiro; Demizu, Yosuke (Frontiers in Chemistry, 2021)
Liver X receptors (LXRs) belong to the nuclear hormone receptor superfamily and function as ligand-dependent transcription factors that regulate cholesterol homeostasis, lipid homeostasis, and immune responses. LXR antagonists are promising treatments for hypercholesterolemia and diabetes. However, effective LXR antagonists and inhibitors are yet to be developed. Thus, we aimed to develop LXR degraders (proteolysis targeting chimeras PROTACs against LXR) as a complementary strategy to provide a similar effect to LXR inhibition. In this study, we report the development of GW3965-PEG5-VH032, a PROTAC capable of effectively degrading LXRprotein. GW3965-PEG5-VH032 induced the ubiquitin-proteasome system-dependent degradation of the LXR protein, which requires VHL E3 ligase. We hope that PROTACs targeting LXR proteins will become novel therapeutic agents for LXR-related diseases.